Development of a balanced instrument to measure global health-related quality of life: The 13-MD - Touré, Moustapha; Lesage, Alain; Poder, Thomas G. (Frontiers in Psychiatry, 2022)
Generic instruments are of interest in measuring global health-related quality of life (GHRQoL). Their applicability to all patients, regardless of their health profile, allows program comparisons of whether the patients share the same disease or not. In this setting, quality-adjusted life-year (QALY) instruments must consider GHRQoL to allow the best programs to emerge for more efficiency in health resource utilization. However, many differences may be perceived among the existing generic instruments relative to their composition, where dimensions related to physical aspects of health are generally depicted more often than dimensions related to mental or social aspects. The objective of this study was to develop a generic instrument that would be complete in its covered meta-dimensions and reflect, in a balanced way, the important aspects of GHRQoL. To this end, a Delphi procedure was held in four rounds, gathering 18 participants, including seven patients, six caregivers, and five citizens. The structure of the instrument derived from the Delphi procedure was submitted to psychometric tests using data from an online survey involving the general population of Quebec, Canada (n = 2,273). The resulting questionnaire, the 13-MD, showed satisfying psychometric properties. It comprises 33 items or dimensions, with five to seven levels each. The 13-MD reflects, in a balanced form, the essential aspects of GHRQoL by including five meta-dimensions for physical health, four meta-dimensions for mental health, three meta-dimensions for social health, and one meta-dimension for sexuality and intimacy. The next step will involve the development of a value set for the 13-MD to allow QALY calculation.